Effect of inoculum concentration on butanol and ethanol production by clostridium acetobutylicum - Baiyinah, A.Talip (2010)
In Malaysia,the government has implement policy instruments aimed at promoting the production of butanol and ethanol as an alternative to renewable energy.The objective was to study the effect of inoculum concentration on butanol and ethanol production and besides that,the study also focused on growth profile of Clostridium acetobutylicum and glucose consumption in POME and RCM.The methods begin with palm oil mill effluent (POME) analysis using High Performance Liquid Chromatography (HPLC).The process continued with the microbial fermentation and each inoculums concentration at 5% v/v,10 % v/v and 15 % v/v were prepared in Reinforced Clostridia Media (RCM).POME as an alternative medium was sedimented for 24 hours, and has been prepared at pH 5.8,diluted with 90 % substrate, deoxygenated the POME using nitrogen gas. Both medium POME and RCM were seeded with different inoculums concentration and after 3 days fermentation, the fermentation broth were undergo liquid-liquid extraction and prepared for Gas Chromatography (GC) analysis.The result obtained from POME analysis showed that galactose was the main component in POME.Moreover,the maximum butanol production for both POME and RCM medium were 0.18533% at 15% v/v (POME) and 0.00801% at 5% v/v (RCM). Result showed that increasing the inoculum concentration would reduce the fermentation time, increased the total glucose consumption and increased the butanol production. While the maximum production of ethanol were,1.87593% at 15% v/v during 40 hours (POME) and 2.36754% at 5% v/v during 60 hours (RCM) of fermentation time.The result showed that there were significant correlation between inoculum concentration and butanol and ethanol production.Thus,itcould be concluded that inoculum concentration does affect the butanol and ethanol production,besides,POME could be an alternative medium for butanol and ethanol fermentation.